HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN MOTIVASI BELAJAR DALAM PROGRAM SEKOLAH LIMA HARI DI SMAN 5 SEMARANG - DIO WIRA PRATAMA; Diana Rusmawati (Jurnal EMPATI, 2017)
This study aims to determine the correlation between peers social support and the motivation of learning in Senior High School students 5, Semarang. Motivation to learn is a psychological condition that generates, moves, directs and maintains the behavior so that individuals do better and more creative so the students will be able to complete the task given by the teacher. Subjects in this study consisted of 119 students of class X which consisted mostly of middle and late adolescents. The sampling technique used by researcher is cluster sampling. This study uses two scales as a measuring tool: Peer Social Support scale (42items; α = 0,926) and Learning Motivation Scale (33 items; α = 0,916). The result of regression analysis shows a significant positive relationship between peer social support and learning motivation. (r = 0,500; p <0.001) Peer social support provides an effective contribution of 25% towards learning motivation.